The efficacy of promoting sustained shared thinking through the use of activity books on parental empowerment; A quasi-experimental study - Kamolvisa Techapoonpon; Wisarat Pruttithavorn; May Sripatanaskul; Niyata Limpiti; Kahwei Yoong (PLoS ONE, 2025)
Background Parental empowerment serves as an essential driving force in promoting child development during the early childhood period. Sustained shared thinking is a method involving two or more individuals engaging in a shared cognitive process through sustained conversation. This principle has proven to be an effective intervention for intellectual stimulation in preschool-aged children. We hypothesize that supporting parents in practicing sustained shared thinking would foster parental empowerment by allowing them to play an active role in the positive change of their children. This study investigates the effectiveness of enhancing sustained shared thinking through self-directed activity books in promoting parental empowerment. Methods This research was a quasi-experimental study conducted from January 2, 2023, to April 24, 2023. The participants (n = 55) were mothers or fathers of children aged four to six years. Each parent received sustained shared thinking-stimulating activity books on a weekly basis over a period of six weeks. Empowerment assessments were made at four points in time: pre-intervention, the third week of intervention, the sixth week of intervention, and three months after completing the intervention. Results Sustained shared thinking-stimulating activity books significantly increased parental empowerment. The mean empowerment score increased from baseline by 30.79% (95% CI [24.66, 36.92]) after three weeks of activities and increased by 115.36% (95% CI [105.19, 125.54]) after six weeks of activities. Empowerment scores remained relatively stable at 114.11% (95% CI [103.9, 124.32]) when assessed three months post-intervention. Conclusions Stimulation of sustained shared thinking through the use of activity books over six weeks significantly increases parental empowerment. The effect of parental empowerment is observable from the third week after the activities and persists for up to three months after the completion of the intervention. The format of this intervention is primarily self-directed activity, providing a solution that can be replicated and further developed in the future. Clinical trial registration: Thai Clinical Trials Registry (TCTR20221203002)